Characteristic cerebral perfusion pattern in neuronal intranuclear inclusion disease - Tai, Hong-Fei; Hua, Tian-Tian; Zhang, Zai-Qiang; Duan, Yun-Yun; Zhuo, Zhi-Zheng; Wang, An; Zhou, Yi; Liu, Shao-Cheng; Lv, Shan (Frontiers in Neuroscience, 2022)
Background: Neuronal intranuclear inclusion disease (NIID), which pathogenesis remains largely unclear, is a neurodegenerative disease caused by GGC repeat expansion in NOTCH2NLC gene. As case studies have reported dynamic cortical perfusion changes in NIID, this study aimed to explore the cerebral perfusion pattern in NIID patients. Methods: A total of 38 NIID patients and 34 healthy controls (HCs) were recruited, and 2 NIID patients who had had episodic symptoms within two months were excluded. Data on demographic characteristics and clinical features were collected. All participants underwent three-dimensional pseudo-continuous arterial spin labeling perfusion magnetic resonance imaging (MRI) scanning. Voxel-based comparisons of cerebral blood flow (CBF) were conducted. Results: NIID patients showed decreased perfusion in the cortex but increased perfusion in the deep brain regions compared with HCs. The regions with significant hypoperfusion were distributed in the bilateral frontal, temporal, parietal, and occipital gyrus, with the left frontal gyrus being the most prominent. The regions with significant hyper-perfusion included the bilateral basal ganglia, midbrain, pons, para-hippocampal, and a part of the bilateral cerebellum, fusiform, lingual, rectus, orbital, and cingulum anterior gyri, which were adjacent to the midline (all FDR-corrected p < 0.05). When comparing the mean CBF value of the whole brain, no significant differences were observed between NIID patients and HCs (28.81 ±10.1 vs. 27.99 ±5.68 ml/100 g*min, p = 0.666). Voxel-based analysis showed no significant difference in cerebral perfusion between NIID patients with and without episodic symptoms. The perfusion within the bilateral middle frontal and anterior cingulate gyri showed positive correlations with MMSE and MoCA scores using age, sex, and education as covariates (p < 0.005 uncorrected). Conclusions: NIID patients exhibited characteristic cortical hypoperfusion and deep brain hyper-perfusion. The perfusion in the bilateral frontal lobe and cingulate gyrus was correlated with the severity of cognitive dysfunction. Cerebral perfusion change may be involved in NIID pathophysiology and serve as a potential indicator for monitoring NIID severity and progression.